Edward Weston - Weston, Edward, 1886-1958.; Cravens, Richard H. (New York : Aperture, 1997)
A collection of black-and-white photographs by twentieth-century photographer Edward Weston, drawn from throughout more than four decades of work.
Copublished by Könemann Verlag.
Includes bibliographical references (p. 94).
Adult
Keywords: Weston, Edward, -- 1886-1958.; Weston, Edward, -- 1886-1958.; Photography, Artistic; Artistic photography